Use of different growth paramaters of Norway spruce (Picea abies (L.) Karst.) to study tree response to climate - Levanič, Tom (Zbornik gozdarstva in lesarstva, 2006)
In the paper, potential analysis of various growth parameters of Norway spruceare introduced at the macro and micro levels. Dendroecological measurements give information as to xylem growth ring widths, their density and content of stable isotopes in the xylem growth rings. Needle trace method of the terminal annual shoot allows retrospective view into needle density ofthe terminal annual shoot and consequently reconstruction of the several parameters linked to the needles and air pollution. Using pinning method, it is possible to follow intra-annual dynamics of the radial growth of trees at the cellular level and furthermore investigate the effect of climatic factorson cambial activity.
Keywords: analize; dendroekologija; metode; Picea abies; Pokljuka; prirastek; smreka